Sikap Agent Of Change Guru & Pegawai di SMK SMTI Padang - Shyfa Rahadathul Aisy; Giska Riva Trifany (GLOBAL SCIENTS PUBLISHER, 2025)
In an era of rapid change, the role of teachers and employees as Agents of Change at SMTI Padang Vocational School is crucial in creating an adaptive and innovative educational environment. The attitude of the Agent of Change reflects a commitment to continue learning, innovating, and being an inspiration to students and colleagues. Teachers and employees who have this attitude are not only able to adapt to the times, but also play an active role in encouraging school progress through creative approaches and future- oriented solutions. Factors such as visionary leadership, teamwork, and the use of technology and the latest learning methods are the main pillars in shaping the character of Agents of Change in the educational environment. By prioritizing a positive attitude and the spirit of change, teachers and employees of SMTI Padang Vocational School are expected to be able to present an education system that is more effective, inclusive, and relevant to the needs of industry and society.